Integration of the circular economy paradigm in companies from the Northwest of the Iberian Peninsula - Sá, Maria Manuel (2022)
Over recent decades, Circular Economy (CE) has become a major topic when organizations try to develop their business amid the constrains of resource limitation and the desire to reduce their environmental impact. This study’s main purpose is to assess the integration of CE practices in public and private organizations in the northwest of the Iberian Peninsula. Through an online survey distributed to 294 companies from the cited region, we assessed their perceptions on CE, including such aspects as the area(s) it was integrated in, why, with what difficulties or what was necessary to accomplish it, and how the impact of the implemented CE practices was measured. Results showed that companies associate CE mostly with “resource optimization”. “Entity’s vision and mission” was the main strategic area where CE was implemented. The main motivation why entities/organizations embraced CE was “environmental reasons”, while “lack of information and guidance” and “lack of financial resources” represented the main obstacles to CE implementation. Non-parametrical statistical tests were used to compare the answers of three groups of people with different positions within the company/entity (manager, executive, and technician), as well as to compare the answers of two activity sectors (industry and services).